Classification of Heavily Damaged Building Damage after Earthquake - Varol Koç (Doğal Afetler ve Çevre Dergisi)
In this study, severe damage types in concrete buildings observed after earthquakes were classified and investigated in relation to the structural behaviors. Since the damage types are very extensive, particularly heavy damages caused by column and combination of beam-column damages were discussed. Classification is made primarily in the form of damage types of the structural system and damages of structural elements. Classification of damage types of structural system was grouped as 1) Overlap collapse related damages, 2) Lateral collapse (accordion) damages, 3) Tilting damages, 4) Failure of a part on vertical alignment type damages, 5) Failure of a part of horizontal alignment type damages and 6) Horizontal failure of entire story while the damages of structural elements were grouped as 1) Out of plane deboning of column and 2) End part damages of column. Beams and floor damages, also considered as structural system damages, are not included in the scope of this study. This study summarizes precautions needed to be taken to prevent such damages studied.